A new wave of Mesoamerican bumblebees? Revising the weisi-complex to reject numts and pseudospecies (Apidae: Bombus) - Williams, Paul H.; Sagot, Philippe; Martínez-López, Oscar; Barajas, Ricardo Ayala-; Mérida-Rivas, Jorge A.; Vandame, Rémy (Zootaxa, 2024)
COI-barcode-like sequences appear to show substantially more species diversity among Mesoamerican bumblebees than had been reported previously from morphological studies. Closer examination shows that some of this apparent diversity may be pseudospecies (groups falsely misinterpreted as separate species), often supported by paralogous ‘numts’ (nuclear copies of mitochondrial sequences). For the well-sampled weisi-complex, we seek to filter out pseudogenes in order to use the orthologous COI-barcode sequences for identifying estimates of evolutionary relationships and likely species’ gene coalescents for candidate species. Even after this filtering, in contrast to recent purely morphological studies our results from an integrative assessment of species’ gene coalescents together with skeletal morphology support that ‘Bombus weisi’ Friese in its recent broad sense consists of two species: B. weisi (which includes the taxon montezumae Cockerell); and B. nigrodorsalis Franklin. Our interpretation rejects likely numts-based pseudospecies and a candidate species that are unsupported by skeletal morphology. This shows that careful attention needs to be paid to both barcode analysis and to skeletal morphology, to avoid describing pseudospecies.